Synergistic Flame‐Retardant Effect of IFR and PPO in Improving Flame Retardancy of Polystyrene. Issue 2 (11th June 2015) - Yan, Hong; Zhang, Jinkai; Zhang, Meng; Du, Xiangxiang; Ma, Senyuan; Xu, Bingshe
ABSTRACT: Intumescent flame retardant (IFR) and polyphenylene oxide (PPO) were used together to enhance the flame‐retardant performance of polystyrene (PS). The IFR system was composed of melamine, ammonium polyphosphate, and pentaerythritol. The results showed that IFR and PPO have a synergistic effect on the flame‐retardant performance of PS. Moreover, the TGA data showed that PPO could promote PS to form more char with higher loading of IFR. Cone calorimeter tests indicated that only the condensed phase played a role in the flame retardancy of PS composites with one additive of IFR or PPO, whereas the flame‐retardant effect of PS composites loaded with PPO and IFR existed in the condensed and gaseous phases due to different char structures.